Accumulation and subcellular distribution of cadmium in rygegrass induced by Aspergillus niger TL-F2 and Aspergillus flavus TL-F3. Issue 3 (23rd February 2022) - Fan, Ting; Liu, Ru; Pan, Dandan; Liu, Yalou; Ye, Wenling; Lu, Hongjuan; Kianpoor Kalkhajeh, Yusef
Abstract: Although plant growth-promoting fungi can greatly accelerate the ryegrass bioaccumulation of cadmium (Cd), the underlying mechanisms are not yet well documented. Therefore, we performed a 20-days hydroponic experiment to investigate the effects of Aspergillus niger TL-F2 ( A. niger TL-F2) and Aspergillus flavus TL-F3 ( A. flavus TL-F3) on accumulation/subcellular distribution of Cd by annual ryegrass Dongmu 70 at different Cd concentrations (0, 2.5, and 5 mg L −1 ). Results indicated that both fungal strains promoted ryegrass biomass/growth by about 60%. Furthermore, we found that ryegrass roots (17.8–37.1 μg pot −1 ) had a significantly higher capability for Cd uptake than the shoots (1.66–5.45 μg pot −1 ) ( p  < 0.05). Of total Cd in ryegrass plants, 44–67% was in soluble form, 24–37% was in cell wall, and 8.5–25.5% was in organelles. Compared with non-fungus ryegrass, cell wall and soluble Cd fractions in fungus-inoculated roots increased and decreased by 13.5–44% and 21.5–26.4%, respectively. Besides, fungus inoculation generally increased the content of cell wall and soluble Cd fractions in ryegrass shoots. Altogether, the study concludes that inoculation of fungus in ryegrass is a promising approach to improve phytoremediation of Cd contaminated environments. Novelty statement Previous study by Han et al. (2018 ) examined the resistance of ryegrass plant to Cd stress after its inoculation with Aspergillus aculeatus . In this study, using a hydroponic experiment, we examined the effects of co-application of two species of Aspergillus fungi. i.e. A. niger TL-F2 and A. flavus TL-F3 on ryegrass growth/biomass, Cd absorption by ryegrass shoots and roots, and subcellular distribution of Cd in ryegrass roots and shoots.